Tidier Drawings of Trees - Edward M. Reingold; John S. Tilford (IEEE Transactions on Software Engineering, 1981)
Various algorithms have been proposed for producing tidy drawings of trees - drawings that are aesthetically pleasing and use minimum drawing space. We show that these algorithms contain some difficulties that lead to aesthetically unpleasing, wider than necessary drawings. We then present a new algorithm with comparable time and storage requirements that produces tidier drawings. Generalizations to forests and m-ary trees are discussed, as are some problems in discretization when alphanumeric output devices are used.